Measurement of the $Υ(1S), Υ(2S)$, and $Υ(3S)$ cross sections in pp collisions at $\sqrt{s}$ = 7 TeV - CMS collaboration (2195 authors) (2013)
The $Υ$(1S), $Υ$(2S), and $Υ$(3S) production cross sections are measured using a data sample corresponding to an integrated luminosity of 35.8 $±$ 1.4 inverse picobarns of proton-proton collisions at $\sqrt{s}$ = 7 TeV, collected with the CMS detector at the LHC. The Upsilon resonances are identified through their decays to dimuons. Integrated over the $Υ$ transverse momentum range $p_{t}^{Υ} \lt$ 50GeV and rapidity range |$y^Υ$| $\lt$ 2.4, and assuming unpolarized Upsilon production, the products of the Upsilon production cross sections and dimuon branching fractions are \begin{equation*}σ(pp → Υ(1S) X) . B(Υ(1S) → μ^+ μ^-) = (8.55 ± 0.05^{+0.56}_{-0.50} ± 0.34) nb,\end{equation*} \begin{equation*}σ(pp → Υ(2S) X) . B(Υ(2S) → μ^+ μ^-) = (2.21 ± 0.03^{+0.16}_{-0.14} ± 0.09) nb,\end{equation*} \begin{equation*}σ(pp → Υ(3S) X) . B(Υ(3S) → μ^+ μ^-) = (1.11 ± 0.02^{+0.10}_{-0.08} ± 0.04) nb, \end{equation*} where the first uncertainty is statistical, the second is systematic, and the third is from the uncertainty in the integrated luminosity. The differential cross sections in bins of transverse momentum and rapidity, and the cross section ratios are presented. Cross section measurements performed within a restricted muon kinematic range and not corrected for acceptance are also provided. These latter measurements are independent of Upsilon polarization assumptions. The results are compared to theoretical predictions and previous measurements.